Order Theory I and II As Foundations for Finding Relationship Between Formulas - Stephanus Ivan Goenawan (Bina Nusantara University, 2020)
Order theory is generated through the process of induction logic from solving several mathematical functions so that it can be formulated in general the pattern of regularity. If there are function and associates each other is organized and interconnected, then the constants will also be organized and interconnected. Similarly, if there are function and associates that are mutually regulated and the constants that make them organized and interrelated, then the function basis and associates will also have interconnected properties.